Treatment adherence and its relationship with health literacy in patients with mood disorders in hospitals affiliated with Isfahan University of Medical Sciences in 2022: A cross-sectional study - Sayed Reza Mousavi; Malek Fereidooni Moghadam; Aliasghar Jamalinasab; Elaheh Farahani; Bahareh Yousefi; Pegah Hassanvand (Shahrekord University of Medical Sciences, 2023)
Background and aims: Mood disorders include major depression and bipolar disorder. Treatment adherence and health literacy are very important in these patients because they may affect their quality of life, performance, and recovery. Therefore, this study aims to determine the level of treatment adherence and its relationship to health literacy in patients with mood disorders. Methods: This cross-sectional-correlation study was conducted on 120 patients with mood disorders in 2021-2022. Data were collected using the treatment adherence questionnaire of Ziaee et al and the Health Literacy of Iranian Adults (HELIA) questionnaire. Finally, the collected data were analyzed in SPSS-16 software. Results: Findings showed that patients with mood disorders had moderate treatment adherence (51.53±8.31) and insufficient health literacy (61.31±15.91). The results indicated that treatment adherence had a significant relationship with health literacy in patients with mood disorders (P<0.05, r: 0.298). Conclusion: Inadequate health literacy in patients with mood disorders shows that health literacy should be considered in improving mental health. Therefore, it is recommended that by promoting the health literacy of these patients and identifying its challenges, treatment adherence in patients with mood disorders be improved.